ANALISIS PENARIKAN GARIS BATAS DAERAH KUDUS DENGAN JEPARA BERDASARKAN PERMENDAGRI NOMOR 25 TAHUN 2012 TERHADAP CITRA TEGAK SATELIT RESOLUSI TINGGI TERMUTAKHIR - Prawira, Chandra Yudha; Bifani, Earlyan Athiyana; Ihsan, Haikal Muhammad; Deliana, Vania Tsani; Putri, Regina Verra Santiara Yahya (Jurnal Samudra Geografi, 2025)
Regional boundaries are an important thing that becomes a supporting factor for development in the development of an area. The implementation of regional autonomy causes problems that often occur related to regional boundaries. The government has issued Peemendagri No. 25 of 2012 which contains Guidelines for Regional Boundary Affirmation. This study aims to analyze the drawing of the boundaries of the Kudus and Jepara areas as a result of delineation with the process of updating regional boundaries using the cytometric method against High -Resolution Satellite Upright Images (CTRST). The results showed that there was a difference in the area of Kudus which was originally 44,700 Ha to 44,815 Ha and Jepara reduced in area with an initial area of 101,953 Ha to 101,838 Ha.